إشارات النبي صلى الله عليه وسلم بأصبعه الواحدة معنويتها ودلالاتها: The Meaning and Implications of Prophet’s (ﷺ) Gestures with One Finger - Hafeez Ullah Abdul Salaam, (Seerat Studies, 2024)
Islam is a comprehensive and complete religion and methodology. There are two main sources for obtaining the teachings of Islam, “Holy Quran and Hadith”. The Hadith revolves around the personality of the Holy Prophet (ﷺ), his sayings, his acts and the acts being performed in front of him and he remained silent and allowed to do such an act. Only the words, sentences, sayings and acts of the Holy Prophet (ﷺ) are to be fully compliant in all respects. Same is the case with the Holy Prophets (ﷺ) gestures, his movements, and postures as they are not even useless. With this logic and claim, the Prophet’s (ﷺ) instructions and acts in this regard have been collected and clarified by Muhadditheen. This article explains and take into consideration the “indications” of the Holy Prophet(ﷺ). Also, the Hadiths in which the word "indication" is commonly used are collected and their meaning and the lessons from them is tried to be explained. The gestures of the Prophet (ﷺ) were used to indicate acts of worship, explanations, training, determination, and the manifestation of grace and mercy. This indicates that the gestures of the Prophet (ﷺ) contained educational, training, and explanatory aspects.